GOVERNMENT LAW IN THE IMPLEMENTATION OF VILLAGE DEVELOPMENT IN WONOKERTO - Rahmadi, R Y Gembong; Sahdan, Gregorius; Firdaus, Mohamad; Etebom, John Monday (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
This study discusses the contradiction between Village Law Number 6 of 2014, which states that villages have the authority to regulate and take care of their own households. However, the regulation clashes with its derivative regulation, namely Permendes Number 21 of 2020 concerning General Guidelines for Village Development and Village Community Empowerment. The contradiction occurs in a clause of the Village Law, namely Village Regulation based on: recognition; subsidiary; Diversity; Togetherness; mutual cooperation; Family; deliberation; democracy; Independence; participation; Equality; Empowerment; and sustainability. The principles of recognition, democracy and independence then clash with the Ministerial Regulation which regulates the policy direction of: Village Development and Village Community Empowerment policy direction; Village Development; Village Community Empowerment; and monitoring, evaluation, supervision, and coaching. This research uses the Theory of Utility, Utility is always associated with Jeremy Benthamdan's theory of utilitarianism and Hans Kelsen's Grundnorm theory. The purpose of the law must meet three aspects, namely Justice, Certainty, and Utility. The research method in this study uses an exploratory qualitative method with the type of case study research. The location of this research was carried out in Wonokerto Village, Kapanewon Turi, Sleman Regency, Special Region of Yogyakarta. The results of this study show that Constructing interests, pragmatism, and formality are often the basis for making a policy. This also happened in the making of Permendes No. 21 of 2020 concerning General Guidelines for Village Development and Village Community Empowerment. The existence of contradictions between one rule and another is a domino effect on the making of government policies under it, even at the village level. Formality policies such as the existence of an application, instead of providing benefits to the village community, actually make it difficult for the community. Villages are increasingly exclusive and the top-down policy is also the impact of the authority of the village which is castrated by the rules under the Village Law.